Perancangan Pembuatan Kemasan dan Labeling Home Industri Olahan Jagung Usaha Kelompok Desa Tonasa Kabupaten Takalar - Nur Ihwan Safutra; Yan Herdianzah; Nurhayati Rauf; Anis Saleh; A.Dwi Wahyuni P; Arfandi Ahmad; Muhammad Fachry Hafid (PT.Mantaya Idea Batara, 2021)
Processed Corn Business so far is very promising for those who cultivate it. If you look at the competitors who are engaged in the same business, there are already quite a lot. With better taste innovations, beautiful and attractive sizes, economical prices, and most importantly healthy and hygienic by providing attractive packaging and labels so that partner products are able to compete and sell well in the market. With the Processed Corn business (corn lunkhead, corn chips, popcorn, etc.) Home Processed Corn Industry Business Group Tonasa Village, Sanrobone District, Takalar Regency which already has regular customers will increase its marketing by making attractive packaging and labels to find markets and even agents who want to sell it, so there will be many who help to develop this corn processing business. The problems faced are (1) not yet given good packaging for processed corn products that are marketed and (2) not yet given labeling to introduce their products.